Analisis Pengelolaan Hutan Kemasyarakatan (HKm) Berbasis Agroforestri oleh Masyarakat Desa Goloworok, Kecamatan Ruteng, Kabupaten Manggarai - Sixta Angrainy Lagur; Nixon Rammang; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Agroforestry is a land management system that integrates forestry, agriculture, and/or livestock components simultaneously or sequentially in one land unit. This system offers a sustainable solution for forest land utilization. This study aims to analyze agroforestry-based Community Forest (HKm) management by the people of Goloworok Village, Ruteng District, Manggarai Regency. Agroforestry is a strategic solution in the productive and sustainable management of protected forest land without changing the function of the region. The methods used include quantitative and qualitative descriptive approaches with sampling techniques using the Slovin formula which produced 62 respondents from 164 members of the Forest Farmers Group (KTH). Data collection was carried out through interviews, observations, and documentation. The results of the study showed that there were two planting patterns applied, namely alternating rows and random mixtures. Most farmers (39 respondents) apply the alternative rows pattern because it is considered more regular and makes it easier to maintain until harvest. The agroforestry systems used include simple agroforestry systems (a combination of trees and one type of seasonal crop) and complex (a combination of various types of trees, agricultural crops, and/or livestock resembling natural forests), and are classified into agrosilvopastures based on a combination of forestry, agriculture, and livestock elements.